Temporal, biomechanical evaluation of a novel, transcatheter polymeric aortic valve in ovine aortic banding model - Kachel, Mateusz; Buszman, Piotr P.; Milewski, Krzysztof P.; Michalak, Magdalena; Domaradzki, Wojciech; Pruski, Maciej; Sobota, Michał; Fernandez, Carlos; Konopko, Marta; Nożyński, Jerzy; Kaźmierczak, Paweł; Włodarczyk, Jakub; et al. (Frontiers in Cardiovascular Medicine, 2022)
Objectives The aim of the study is to evaluate the functionality, durability, and temporal biocompatibility of a novel, balloon-expandable polymeric transcatheter heart valve (ATHV) system (InFlow, CardValve Consortium, Poland). Along with expanding TAVI indications, the demand for new transcatheter valves is increasing. Methods A surgical ascending aortic banding model was created in 20 sheep. Two weeks later, 16 sheep were implanted with ATHV systems (15–16F). Three animals were euthanized after a 30-day follow-up, four animals after a 90-day follow-up, and six animals after a 180-day follow-up. A follow-up transthoracic echocardiography (TTE) was performed. Results There was one procedure-related (6,25%) and two model-related deaths (12,5%; banding site calcification with subsequent infection originating externally from banding). TTE revealed the flow gradients (max/average) of 30,75/17,91; 32,57/19,21; and 21,34/10,63 mmHg at 30, 90, and 180 days, respectively. There were two cases of low-degree regurgitation after 180 days with no perivalvular leak observed. Histopathological analysis showed no valve degeneration at terminal follow-up with optimal healing. Small thrombi were present at the aortic wall adjacent to the base of the leaflets, and between the aortic wall and the stent in most of the valves; however, leaflets remained free from thrombi in all cases. Scanty calcifications of leaflets were reported in three animals evaluated 180 days after implantation. Conclusion This preclinical study in the aortic banding model showed good hemodynamic performance, durability, and biocompatibility of the novel ATHV. Furthermore, regulatory studies with longer follow-ups are warranted.